Effectiveness Of Video Media And Leaflets On Knowledge About Breast Massage Techniques In Postpartum Mothers At Gempol Health Center In 2022 - Ine Sukmasari; Lili Farlikhatun (International Journal of Medicine and Health, 2023)
Backgrounds : The puerperium is the period after childbirth, which is counted from after the placenta has come out, the puerperium is also called the recovery period, where the uterine devices will recover as before. Providing information about breast massage techniques to the public, especially to postpartum mothers is very important. Therefore efforts to provide information about breast massage techniques can be done through health promotion efforts. The results of a preliminary study conducted by researchers at the Gempol Health Center on 5 postpartum mothers using a questionnaire, of the 5 questions asked, 5 postpartum mothers answered that they did not know how to increase milk with breast massage techniques. Research Objectives : To find out the effectiveness of video media and leaflets on knowledge about breast massage techniques for postpartum women at the Gempol Health Center in 2022 Research Methods:This type of research is quantitative with a quasi-experimental research design and a pretest-posttest group design. The pop ulation in this study was 117 postpartum mothers who were at the Gempol Health Center. The sample in this study were 54 respondents. Bivariate analysis using the Wilcoxon test. Research results : The description of postpartum mothers' knowledge about breast massage techniques after being given leaflet media was mostly lacking as many as 32 people (59.3%). Postpartum mothers' knowledge about breast massage techniques after being given video media was mostly as good as many as 44 people (81.5%). Conclusions and Suggestions : It can be concluded that video media is more effective for increasing knowledge about breast massage techniques in postpartum mothers than media leaflets. It is recommended that managing midwives facilitate mothers in receiving health counseling/education especially for postpartum mothers regarding breast massage techniques during the postpartum period.